The Mosi Integral: Gagasan M. Natsir Dalam Mempersatukan Indonesia Tahun 1950 - Adli, Syahrul (Edu Sosial, 2023)
This research aims to depict M. Natsir ideas in advocating for the restoration of the unitary state of the Republic of Indonesia, which was previously a federated state composed of 16 constituent states, throught the concept of the integral motion. The method employed in this research is a literature study, involving the examination of existing literature which is then analyzed to reconstruct history. The findings of the research indicate that the integral motion is a concept that advocate for the reunification of the federated Indonesian state, consisting of 16 constituent state, into the Unitary State of the Republic of Indonesian. In order to achieve this unified state, M. Natsir first had to embark on a political journey from one constituent state t another, seeking solution to the stateâ€™s turmoil at that time. The concept of the Integral Motion essentially represented tha aspirations of theÂ  Indonesia people, yet fears of the consequences that might ensue still lingered. However, M. Natsir was able to persuade the government, parliament, and key figures of the nation, leading to the presentation of this concept before the RIS (United State of Indonesia) parliament on April, 1950.